Reliability and Validity of the Functional Assessment of Currently Employed Technology Scale (FACETS) - Lepkowsky, Charles M.; Arndt, Stephan (Issues and Developments in Medicine and Medical Research Vol. 5, 2022)
Introduction: Health protocols have not included technology as a specific area of assessment or treatment. The Functional Assessment of Currently Employed Technology Scale (FACETS) was created for this purpose. FACETS is a ten-item questionnaire that assesses five functional domains. The current study was carried out to determine the validity and reliability of FACETS. Methods: Using 423 previously deidentified FACETS forms from clinical records, analyses such as Cronbach's alpha, McDonald's omega, confidence intervals for alpha and omega, multiple group factor analysis, Fleming's index of scale fit, and differential item (domain) function were carried out (DIF). Results: Internal consistency and factor validity for the 10 FACETS items and intra-domain correlations were high. The factor scale fit index calculated by Fleming indicated an excellent fit. With the exception of one domain, all domains contain enough unique information to produce differential item functioning. Discussion and Conclusions: For the five domains, FACETS demonstrated high internal consistency reliability, strong general factor validity, and strong factor validity.